2013
DOI: 10.33073/pjm-2013-007
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Some Fusarium Species Associated with Superficial Blemishes of Potato Tubers

Abstract: A b s t r a c tAs an organ for reserve and propagation, the tuber grows underground and is in contact with soil-borne microorganisms, making it potentially exposed to blemishes. erefore, the objective of this study was the possibility of using some modern methods of molecular diagnostics and detection of the presence of fungal contaminants in potato blemishes in Al-Qasim (Saudi Arabia). Polygonal lesions were the most observed blemish type in the collected samples. One hundred and sixty isolates were recovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This result is in agreement with several auhtors [13,45,46] who reported that F. sambucinum and F. oxysporium were the most frequently Fusarium species associated with potato dry rot in Egypt. According to Gashgari and Gherbawy [32] isolated Fusarium oxysporum, F. redolens, F. solani, F. sambucinum and F. graminearum from Saudi potato tubers. However, the genus Fusarium is complex and morphological differences may be difficult to observe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in agreement with several auhtors [13,45,46] who reported that F. sambucinum and F. oxysporium were the most frequently Fusarium species associated with potato dry rot in Egypt. According to Gashgari and Gherbawy [32] isolated Fusarium oxysporum, F. redolens, F. solani, F. sambucinum and F. graminearum from Saudi potato tubers. However, the genus Fusarium is complex and morphological differences may be difficult to observe.…”
Section: Discussionmentioning
confidence: 99%
“…Bayona et al [62] confirmed the pathogenicity of two F. oxysporum isolates associated with potato dry rot in Colombia. Gashgari and Gherbawy [32] recorded that Fusarium oxysporum strains (KAUF12.1, KAUF12.2, KAUF12.3 and KAUF12.4) isolated from Suadi potato tubers did not show any pathogenicity against tubers. Chehri et al [63] in Malaysia studied the occurrence and pathogenicity of Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is responsible for severe vascular wilts, and can cause tuber rot. Reduction of the yield caused by dry rot is on average 6%, with possible losses up to 25% (Gashgari & Gherbawy 2013), while almost complete loss of stored commercial potatoes varieties was reported in Turkey (Eken et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1515/plass-2017-0021 Pathogenicity tests are often described in literature, but no unified dry rot resistance assay has been presented. The differences cover inoculum preparation (conidial suspension, agar plugs with Fusarium mycelium), temperature (4°C , 10°C, 16°C, 20°C) and time (20, 21, 30, 35 days) of incubation or lesion size scoring (depth of necrosis, depth and width averages, lesion in mm 2 , rot volume in mm 3 , 1-9 scale according to the percentage of the diseased area); common conditions comprise the absence of light and maintenance of high relative humidity during the incubation period (Gachango et al, 2012;Gashgari and Gherbawy, 2013;Peters et al, 2008a;Peters et al, 2008b;Du et al, 2012;Zarzycka, 2001). Instead of wounded tubers, tuber slices inoculated with inoculum plugs have also been proposed for pathogenicity tests (Desjardins and Gardner, 1989).…”
Section: Introductionmentioning
confidence: 99%